2001
DOI: 10.1086/320329
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Metallicity Relation for the Local Group Dwarf Spheroidal Galaxies: A New Picture for the Chemical Enrichment of Galaxies in the Lowest Mass Range

Abstract: The virial mass (M vir )-metallicity relation among the Local Group dwarf spheroidal galaxies (dSphs) is examined. Hirashita, Takeuchi, & Tamura showed that the dSphs can be divided into two distinct classes with respect to the relation between their virial masses and luminosities: low-mass (M vir 10 8 M ⊙ ) and highmass (M vir 10 8 M ⊙ ) groups. We see that both the mass-metallicity and the massluminosity relations of the high-mass dSphs are understood as a low-mass extension of giant ellipticals. On the cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…It is evident then that some mechanism for gas loss must be adopted. Therefore galactic winds as proposed in our scenario and already suggested by other authors to also explain the observed relation between [O/H] and the mean velocity dispersions in several types of dynamically hot galaxies as well as the massmetallicity relation in dSph galaxies (Richer et al 1998;Tamura et al 2001), seem to be a reasonable solution.…”
Section: Discussionsupporting
confidence: 84%
“…It is evident then that some mechanism for gas loss must be adopted. Therefore galactic winds as proposed in our scenario and already suggested by other authors to also explain the observed relation between [O/H] and the mean velocity dispersions in several types of dynamically hot galaxies as well as the massmetallicity relation in dSph galaxies (Richer et al 1998;Tamura et al 2001), seem to be a reasonable solution.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with the results of Teyssier et al (2009) obtained via cosmological simulations we find that a tiny minority of massive satellites produces the overwhelming majority of HVSs. Given that more massive galaxies are usually also more metal-rich (Tamura et al 2001) we conclude that an intragalactic stellar population should have at least on average a higher metalicities than the surviving dwarf galaxy population.…”
Section: Discussionmentioning
confidence: 80%
“…A possible link between dSphs and giant ellipticals was suggested by Tamura et al (2001), who showed that both the mass-metallicity and mass-luminosity relations of some dSph galaxies may be understood as a low-mass extension of giant elliptical galaxies.…”
Section: Implications For the Formation Of The Giant Galaxiesmentioning
confidence: 99%